2005
DOI: 10.1016/j.ejcts.2004.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Pitfall in the computed-tomography-diagnosis of postcardiotomy infection: iodine accumulation after irrigation mimicking retrosternal abscess

Abstract: Bauernschmitt and colleagues [1] present an interesting experience, which been underreported until now. As a matter of fact there are numerous reports of mediastinal irrigation with iodine solution for mediastinitis [2][3][4][5]. Everybody knows that many contrast media used for angiography or computed tomography are based on water-soluble iodinated solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Misawa et al showed that a mediastinal soft tissue mass combined with a bilateral pleural effusion can be a characteristic CT finding in poststernotomy infectious mediastinitis, and that chest CT is more sensitive for detecting sternal dehiscence, sternal erosion, and subcutaneous fluid accumulation. Erroneous diagnoses due to surgical packing, surgical (manufactured by Ethicon—A Johnson & Johnson Family of Companies, Piscataway, NJ, USA), body foreign reaction, or iodine accumulation following irrigation have been reported.…”
Section: Evidence Of Infectionmentioning
confidence: 99%
“…Misawa et al showed that a mediastinal soft tissue mass combined with a bilateral pleural effusion can be a characteristic CT finding in poststernotomy infectious mediastinitis, and that chest CT is more sensitive for detecting sternal dehiscence, sternal erosion, and subcutaneous fluid accumulation. Erroneous diagnoses due to surgical packing, surgical (manufactured by Ethicon—A Johnson & Johnson Family of Companies, Piscataway, NJ, USA), body foreign reaction, or iodine accumulation following irrigation have been reported.…”
Section: Evidence Of Infectionmentioning
confidence: 99%
“…CT scans have been considered of great value to localize infected tissues [52] , however, there is also some doubt about the validity of a CT scan in performing an early diagnosis [53,54] . Furthermore, erroneous diagnoses due to Surgicel packing [55] , to Surgicel body foreign reaction [56] or to iodine accumulation following irrigation [57] have been reported.…”
Section: Diagnosismentioning
confidence: 99%